Doing-together with words: the sequential unfolding of a moment of meeting in a psychoanalytic therapy session - Herrera, Marcos; Ugarte, Andrea; Vásquez-Torres, Gabriela; Durand, Kene M.; Sánchez, Miguel (Frontiers in Psychology, 2023)
Changes in psychoanalytic therapy have been traditionally attributed to self-knowledge (insight) in the client, provided by the therapist’s interpretations. In recent years there has been growing realization that such changes can also be the consequence of the development of new forms of relatedness through client–therapist interaction, particularly through special intersubjective moments called moments of meeting. Drawing on the methods and findings of Conversation Analysis about the sequential organization of psychotherapeutic interaction, this single-case study examines the unfolding of a moment of meeting in the final session of a brief psychoanalytic therapy in Peru (in Spanish) with a female client victim of domestic violence. Our analysis shows that the moment of meeting, which resolves a challenge to the intersubjective relationship posed by a now moment, comes about interactionally through a sequentially accomplished shared practice of co-animation. In this sequence the client, who had previously assumed a passive role, exercises her own agency to assume an active role, which the therapist ratifies through his response. In this way, a momentary but significant transformation in the here-and-now relationship between client and therapist occurs. Thus, our analysis contributes to the understanding of how a transformation of relation—the transitory emergence of a new form of relatedness—can take place in and through sequentially organized talk and action in psychotherapy. Our study also sheds light on the role of language in moments of meeting, as the moment of meeting in our segment does not occur in parallel with the exchange of linguistic utterances between client and therapist, but through the exchange of such linguistic utterances and through the sequence of actions carried out by that exchange. In this way, the sequential doing-together with words leads to a moment of meeting, bringing about change, at least momentarily, in the implicit ways-of-being-with-others of the client.